Oxidative stress and antioxidant capacity in sickle cell anaemia patients receiving different treatments and medications for different periods of time - Belini Junior, Edis [UNESP]; da Silva, Danilo Gruenig Humberto [UNESP]; Torres, Lidiane de Souza; de Almeida, Eduardo Alves [UNESP]; Cancado, Rodolfo Delfini; Chiattone, Carlos; Bonini-Domingos, Claudia Regina (Springer, 2012)
To evaluate, in a longitudinal study, the profile of lipid peroxidation and antioxidant capacity markers in sickle cell anaemia patients receiving different treatments and medication over different time periods. The three groups were: patients undergoing transfusion therapy and receiving iron chelator deferasirox (DFX group, n = 20); patients receiving deferasirox and hydroxyurea (DFX + HU group, n = 10), and patients receiving only folic acid (FA group, n = 15). Thiobarbituric acid-reactive substance (TBARS) assays and trolox-equivalent antioxidant capacity (TEAC) assays were evaluated during two different periods of analysis, T0 and T1 (after similar to 388 days). Higher FA group TBARS values were observed compared with the DFX + HU group (p = 0.016) at T0; and at T1, higher FA group TBARS values were also observed compared with both the DFX group (p = 0.003) and the DFX + HU group (p = 0.0002). No variation in TEAC values was seen between groups, at either T0 or T1. The mean values of TBARS and TEAC for both the DFX and DFX + HU groups decreased at T1. The antioxidant effects of HU and DFX were observed by through an increase in TEAC levels in DFX and DFX + HU groups when compared with those of normal subjects. Increased TEAC values were not recorded in the FA group, and lipid peroxidation was seen to decrease after DFX and HU use.
Keywords: Sickle cell anemia; Oxidative stress; Hydroxyurea; Deferasirox; Folic acid